ENVIRONMENTAL PROBLEMS OF UZBEKISTAN AND SOLUTION TO THEIR PROBLEMS - Nasibakhan Baymirzaevna Narmyrzaeva; Saodat Madaminovna Rakhimova; Sevara Makhmatkobilovna Rakhmatova (Western European Studies, 2024)
A new approach to the problem of preparing absorbents for fluoride gases in industrial production is proposed and scientifically substantiated, based on the rational use of mechanochemical methods of influencing the molding system and making it possible to obtain cheap, highly active sorbents for the sanitary purification of waste gases
Keywords: environmental; harmful gases; production; methods